A New Method for In Situ Measurements of Oxygen Isotopologues of Soil Water and Carbon Dioxide with High Time Resolution. Issue 8 (21st August 2015) - Gangi, Laura; Rothfuss, Youri; Ogée, Jerôme; Wingate, Lisa; Vereecken, Harry; Brüggemann, Nicolas
Abstract : The oxygen isotope composition of atmospheric CO2 (δ 18 Oac ) can be used to disentangle ecosystem component CO2 fluxes, such as soil respiration and plant assimilation, because the δ 18 O composition of different water pools is transferred to CO2 during isotopic equilibration. The oxygen isotope exchange between CO2 and water in soils has been widely studied with theoretical models, but experimental data are scarce, albeit indispensable to characterization of the role of soils in determining δ 18 Oac . Here, we present a new methodology to monitor the δ 18 O of soil CO2 (δ 18 Osc ) and of soil water (δ 18 Osw ) in situ at varying soil water content. Infrared laser spectroscopy was combined with gas‐permeable polypropylene (PP) tubing installed at different depths in a sand column. The permeable tubing did not lead to any isotopic fractionation and was suitable for combined δ 18 Osc and δ 18 Osw measurements. Soil water became gradually 18 O enriched from the top of the sand over several days. Measured and δ 18 Osc simulated with the model MuSICA indicated incomplete CO2 –H2 O isotopic equilibrium. Irrigation of the sand column with tapwater resulted in a temporary reset of δ 18 Osw along the soil column, while δ 18 Osc was only influenced when the enzyme carbonic anhydrase was added to the irrigation water. Our study demonstrates that δ 18 Osc and δ 18 Osw can now be monitored in situ and online with high time resolution with minimum disturbance. With this new tool at hand, research into the oxygen isotope exchange between soil water and CO2 in natural soils has the potential to advance to a new stage and help to constrain the atmospheric CO2 budget.